ENERGY-CONSCIOUS PRODUCTION SCHEDULING FOR FABRICATED METAL PRODUCTS: A MIXED-INTEGER PROGRAMMING APPROACH - Bobby Kurniawan; Melina Melina; Yusraini Muharni (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Energy is a fundamental requirement in the metal fabrication industry. However, energy consumption is rarely taken into account in production scheduling decisions. In fact, a well-designed production schedule can contribute significantly to energy conservation. Therefore, production scheduling must explicitly consider energy consumption. This study proposes an energy-conscious production scheduling system for a fabricated metal products industry. The production system under study exhibits the characteristics of a hybrid flow shop, and thus the problem is modeled as a hybrid flow shop scheduling problem. To solve this problem, the mixed-integer programming (MIP) method is employed to solve the hybrid flow shop scheduling model. The results demonstrate an energy cost saving of 0.66% compared to the scheduling practice currently in use.